The use of the WHO criteria to detect severe malaria among patients clinically diagnosed with uncomplicated malaria. - Enoch Aninagyei; Richard Harry Asmah; Kwabena Obeng Duedu; John Gameli Deku; Kelvin Senyo Tanson; Yobo Mireku; Fred Gbadago; Desmond Omane Acheampong (Public Library of Science (PLoS), 2024)
The World Health Organization (WHO) strict defining criteria were used to identify severe malaria among Ghanaian patients clinically diagnosed as uncomplicated malaria. From each study participant, blood haemoglobin (Hb) and plasma bilirubin levels were estimated using automated analyzers. According to the WHO, the criteria for diagnosing severe malaria among children (< 12 years) was assessed using Hb < 5 g/dL and among other patients ≥ 12 years, Hb < 7 g/dL with parasitemia > 10,000/μL, plasma bilirubin > 50 μmol/L amidst parasitemia > 100,000/μL and P. falciparum hyperparasitaemia (> 500,000 parasites/μL). Patients initially diagnosed with asymptomatic malaria (n = 347) were recruited. The parasitemia range was 540-863,402 parasite/μL. Overall, 86.2% of the patients had uncomplicated malaria while 13.8% of the patients were diagnosed with severe malaria of various origins. In children < 12 years, 10.8% (17/157) had Hb < 5g/dL with parasitaemia < 10,000 parasites/μL and in other patients (≥ 12 years), 6.3% (12/190) of them recorded Hb < 7g/dL with parasitaemia < 10,000 parasites/μL. Furthermore, 13.8% (48/347) had serum bilirubin levels > 50 μmol/L with parasitemia > 100,000/μL. In all the patients with hyperbilirubinemia, Hb levels fell below either 5g/dL or 7g/dL, for patients less than and 12 years or more, respectively. Finally, 1.7% (6/347) of the patients with malaria had parasite counts (> 500,000 parasites/μL). Irrespective of the etiology, patients diagnosed with severe malaria presented with pallor, vomiting, diarrhea, chills, fever and nausea, concurrently. Without comprehensive laboratory evaluation, patients with severe malaria could be misdiagnosed. Therefore, healthcare facilities need adequate human and logistical resources to be able to diagnose severe malaria for appropriate management to avert any untoward outcomes.